2010
DOI: 10.1111/j.1752-4571.2010.00119.x
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide invasion by the little fire ant: routes of introduction and eco‐evolutionary pathways

Abstract: Biological invasions are generally thought to occur after human aided migration to a new range. However, human activities prior to migration may also play a role. We studied here the evolutionary genetics of introduced populations of the invasive ant Wasmannia auropunctata at a worldwide scale. Using microsatellite markers, we reconstructed the main routes of introduction of the species. We found three main routes of introduction, each of them strongly associated to human history and trading routes. We also de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
83
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(90 citation statements)
references
References 65 publications
(120 reference statements)
6
83
0
1
Order By: Relevance
“…Second, this mechanism maintains high levels of heterozygosity and/or beneficial genetic combinations over time in the sexually produced worker offspring. In agreement with this, Foucaud et al [16,27] found that heterozygosity, in workers from clonal populations, is on average higher than that in sexual 107 (5) 40 (5) 31 (4) type of crosses rspb.royalsocietypublishing.org Proc R Soc B 280: 20131181…”
Section: Resultssupporting
confidence: 55%
“…Second, this mechanism maintains high levels of heterozygosity and/or beneficial genetic combinations over time in the sexually produced worker offspring. In agreement with this, Foucaud et al [16,27] found that heterozygosity, in workers from clonal populations, is on average higher than that in sexual 107 (5) 40 (5) 31 (4) type of crosses rspb.royalsocietypublishing.org Proc R Soc B 280: 20131181…”
Section: Resultssupporting
confidence: 55%
“…In addition to theoretical expectations (Lee and Gelembiuk 2008), the high invasion success of invaders from disturbed environments has been shown in recent empirical studies (Foucaud et al 2010). Findings from plant invasion studies (Burke andGrime 1996, Davis et al 2000) and microbial invasions (Liu et al 2012, Li andStevens 2012) support the theories of high invasibility of disturbed environments (Elton 1958, Davis 2009).…”
Section: Evolutionary History Of the Invader And The Community Speciementioning
confidence: 83%
“…Unicoloniality is also typified by the lack of aggression, even between very distant nests e.g., Linepithema humilis (Giraud et al, 2002;Brandt et al, 2009b;Blight et al, 2012), Wasmannia auropunctata (Errard et al, 2005;Vonshak et al, 2009;Foucaud et al, 2010) or Pheidole megacephala (Fournier et al, 2009). This is attributed to the relaxation or complete loss of nestmate recognition in these population, the mechanism of which is postulated to be either "genetic cleansing" following introduction (Giraud et al, 2002) or a "bottleneck" phenomenon (Suarez et al, 2008).…”
Section: Introductionmentioning
confidence: 99%